2014
DOI: 10.4314/ajtcam.v11i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Restoration Of Glutamine Synthetase Activity, Nitric Oxide Levels And Amelioration Of Oxidative Stress By Propolis In Kainic Acid Mediated Excitotoxicity

Abstract: Background: Propolis has been proposed to be protective on neurodegenerative disorders. To understand the neuroprotective effects of honeybee propolis, glutamine synthetase (GS) activity, nitric oxide (NO), thiobarbituric acid reactive substances (TBARS) and total antioxidant status (TAS) were studied in different brain regions-cerebral cortex (CC), cerebellum (CB) and brain stem (BS) of rats supplemented with propolis and subjected to kainic acid (KA) mediated excitotoxicity. Materials and Methods: Male Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Other study on propolis, which is another beehive product, appeared to be effective in preventing KA-induced neuronal loss in the regions of the hippocampus [11]. In addition, propolis was found to attenuate KA-induced seizures and KA-induced oxidative stress in the brain thought to be due to its antioxidant property [11, 38]. These studies suggested that these antioxidants provide protection against KA-induced neuronal degeneration and seizures through antioxidant mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Other study on propolis, which is another beehive product, appeared to be effective in preventing KA-induced neuronal loss in the regions of the hippocampus [11]. In addition, propolis was found to attenuate KA-induced seizures and KA-induced oxidative stress in the brain thought to be due to its antioxidant property [11, 38]. These studies suggested that these antioxidants provide protection against KA-induced neuronal degeneration and seizures through antioxidant mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…ese beneficial effects of propolis could have been attributed to its bioactive compounds as well as the combined actions of these compounds [69]. Propolis has been reported to attenuate nitric oxide level, glutamine synthetase activity, oxidative stress, tumor necrosis factor-alpha (TNF-α), and caspase-3 activity, reduce seizures, and prevent neuronal loss in kainic acid-induced excitotoxicity rat model [74][75][76]. ese findings suggested that propolis exhibits its inhibitory effect on the oxidative stress, proinflammatory cytokines, and apoptosis as well as protection against neuronal damage through its anti-inflammatory, antioxidant, and antiapoptotic properties.…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…It was subjected to 80% ethanol extract as per the procedure of Isla et al (2001) as described by Swamy et al (2014). Single lot of propolis was used for extraction and used for administration to rats.…”
Section: Propolis Collection and Ethanol Extractionmentioning
confidence: 99%